Regulation of Criminal Sanctions for Physical Domestic Violence Promoting Gender Equality - Fandy Setiawan; Hery Purwanto; Hariyanto Hariyanto; Bambang Prasetyo; Muhammad Azam (Contrarius Indonesia, 2026)
Victims of physical domestic violence experience unequal power relations, economic vulnerability, and social stigma, requiring a criminal justice system that ensures offender accountability, victim protection, recovery, and substantive justice. This study examines the extent to which the current regulation of criminal sanctions for physical domestic violence reflects the values of Pancasila justice, identifies the weaknesses of the existing legal framework, and formulates a regulatory reconstruction based on the principles of Pancasila justice. This research adopts a sociolegal approach by examining statutory regulations, legal doctrines, and their practical implementation through qualitative analysis of legal materials and empirical findings. The results show that first, the existing regulation under Law Number 23 of 2004 continues to emphasize imprisonment and monetary penalties while failing to provide comprehensive protection through restitution, psychological rehabilitation, health services, legal assistance, and victim recovery. Second, weaknesses in legal substance, institutional effectiveness, and legal culture reduce the effectiveness of law enforcement and limit victims' access to meaningful legal protection and justice. Third, reconstructing the criminal sanction framework by establishing restitution as the primary sanction, strengthening additional sanctions through movement restrictions and mandatory counseling, reclassifying complaint based offenses as ordinary offenses, and developing effective restitution enforcement mechanisms creates a victim oriented criminal justice system that enhances legal certainty, promotes substantive justice, and realizes the humanitarian, equality, and social justice values embodied in Pancasila.